2020
DOI: 10.1007/s00382-020-05481-2
|View full text |Cite
|
Sign up to set email alerts
|

Context of the added value in coupled atmosphere-land RegCM4–CLM4.5 in the simulation of Indian summer monsoon

Abstract: The potential of the RegCM4-CLM4.5 model for value addition over the MIROC5 GCM for Indian Summer Monsson (ISM) simulation for the present climate has been examined. The added value has been investigated in terms of the added value index (AV) and the Modified Brier Skill Score (MBSS). In general, a strong dry (wet) bias > 5 mm/day in the RegCM4 (MIROC5) dataset was prevalent over different parts of India. Additional precipitation statistics such as the area-averaged mean, standard deviation, correlation coeff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 90 publications
(98 reference statements)
0
6
1
Order By: Relevance
“…However, the ROM 0.11 shows an increase of dry bias over the central part of the NEI, probably due to the limitation of using the hydrostatic version at a higher resolution over the region with a complex interaction between the convective system and large-scale dynamics (Maurya et al, 2018). The magnitude of bias reported in this study is considerably less than that of the bias reported in earlier studies using RCM (Lucas-Picher et al, 2011;Kumar et al, 2014a, 2014b, 2014c, Bhatla et al, 2020Kumar and Dimri, 2020) and coupled regional atmosphere-ocean model/RESM (Misra et al, 2017(Misra et al, , 2018Di Sante et al, 2019;Mishra et al, 2021).…”
Section: Mean Monsoonal Characteristics and The Added Valuecontrasting
confidence: 67%
“…However, the ROM 0.11 shows an increase of dry bias over the central part of the NEI, probably due to the limitation of using the hydrostatic version at a higher resolution over the region with a complex interaction between the convective system and large-scale dynamics (Maurya et al, 2018). The magnitude of bias reported in this study is considerably less than that of the bias reported in earlier studies using RCM (Lucas-Picher et al, 2011;Kumar et al, 2014a, 2014b, 2014c, Bhatla et al, 2020Kumar and Dimri, 2020) and coupled regional atmosphere-ocean model/RESM (Misra et al, 2017(Misra et al, , 2018Di Sante et al, 2019;Mishra et al, 2021).…”
Section: Mean Monsoonal Characteristics and The Added Valuecontrasting
confidence: 67%
“…In this context, the added value (AV) is defined as a measure of the extent to which the reduced‐scale climate representation is closest to observation than the model that served as a lateral forcing (Di Luca et al, 2012, 2016; Falco et al, 2020; Lucas‐Picher et al, 2017). Although some works point to AV of the RCM, particularly in the representation of precipitation in terrain with complex topography (e.g., Feser et al, 2011; Fotso‐Nguemo et al, 2017; Kumar & Dimri, 2021; Rummukainen, 2016), other studies find deterioration (e.g., Coppola et al, 2014; Mishra et al, 2014; Singh et al, 2017). These results depend on many factors, that is, the regional model adopted, the study area, the hydrological regime, the configuration adopted in the experiment, the analysed variable, the temporal and spatial scale, the method used to analyse the experiment and the set of data used as LBC (Giorgi & Gutowski, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…DASCAT is advantageous due to its consistent temporal coverage with ERA-Interim over the study period. Since modified BSS was introduced to evaluate the added value of sea surface wind hindcast [20], many studies used modified BSS to evaluate added value quantitatively [13,21,22,57,58].…”
Section: Evaluation Methodsmentioning
confidence: 99%